2005
DOI: 10.1038/sj.pcan.4500835
|View full text |Cite
|
Sign up to set email alerts
|

Targeting epitopes in prostate-specific membrane antigen for antibody therapy of prostate cancer

Abstract: Prostate-specific membrane antigen (PSMA) is a target for immunotherapy of prostate cancer. It has been shown that antibodies against PSMA inhibited the in vivo growth of LNCaP tumor. In the present study, monoclonal antibodies against four epitopes in PSMA were raised. MAb 24.4E6 (IgG1), specific for the epitope (residues 638-657) in PSMA, significantly reduced the growth rate of established LNCaP tumor in SCID mice. Mouse IgG was detected in the tumor of mice treated with 24.4E6, but not with an unrelated MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Xenotransplants of cancer cell lines grown in immune-deficient mice or rats are often considered as counter-parts to poorly differentiated metastases of prostate cancers (14,15). However, poorly differentiated prostate cancer cells in metastases contain cells which still have the ability to produce prostasomes (16,17), but our xenotransplants did not demonstrate any prostasomes-containing cells.…”
Section: Discussionmentioning
confidence: 39%
“…Xenotransplants of cancer cell lines grown in immune-deficient mice or rats are often considered as counter-parts to poorly differentiated metastases of prostate cancers (14,15). However, poorly differentiated prostate cancer cells in metastases contain cells which still have the ability to produce prostasomes (16,17), but our xenotransplants did not demonstrate any prostasomes-containing cells.…”
Section: Discussionmentioning
confidence: 39%
“…Among these 20 genes, six are well‐known androgen‐regulated genes (ARG)—AR, PSMA, HOXB13, NKX3‐1, CITED2, UGT2B15 (Nelson et al , 2002; Velasco et al , 2004)—which have been shown to mediate metastatic disease progression. For example, PSMA (also known as FOLH1), prostate‐specific membrane antigen 1, is used as a diagnostic and prognostic indicator for prostate cancer and is associated with prostate cancer aggressiveness and metastasis (Burger et al , 2002; Schmittgen et al , 2003; Kinoshita et al , 2005). HOXB13, homeobox B13, has been implicated in progression and metastasis in prostate cancer (Jung et al , 2004; Edwards et al , 2005; Zhao et al , 2005) and found to function as an AR repressor, modulating AR signaling (Jung et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In the following years great efforts were undertaken to develop mAbs against the extracellular domain of PSMA. Summarizing these efforts, numerous papers describing in detail the mAbs different characteristics have been published [72][73][74][75][76][77]. Of these, the mAbs J591, J533, J415, D2B, 107-1A4, E99, 3/A12, 3/E7, 3/F11 and 3E6 have been shown to bind the most efficiently to cell-surface PSMA.…”
Section: Antibodiesmentioning
confidence: 99%